1987
DOI: 10.1016/0014-5793(87)81150-x
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of bacterial cellulases prevents proteolytic cleavage between functional domains

Abstract: Glycosylatedcellulases from Celhdomonas jimi were compared with their non-glycosylated counterparts synthesized in Escherichia coli from recombinant DNA. Glycosylation of the enzymes does not significantly affect their kinetic properties, or their stabilities towards heat and pH. However, the glycosylated enzymes are protected from attack by a C.fimi protease when bound to cellulose, while the non-glycosylated enzymes yield active, truncated products with greatly reduced affinity for cellulose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
98
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(101 citation statements)
references
References 13 publications
3
98
0
Order By: Relevance
“…The secretion of proteases aids in the competition for resources and also is a means for pathogen defense mechanisms (46). It is clear from previous studies that glycans can protect against proteolysis (20,42). Our results also show such protection, showing that glycans can protect the peptide backbone from proteolytic attack, likely through a steric hindrance mechanism.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The secretion of proteases aids in the competition for resources and also is a means for pathogen defense mechanisms (46). It is clear from previous studies that glycans can protect against proteolysis (20,42). Our results also show such protection, showing that glycans can protect the peptide backbone from proteolytic attack, likely through a steric hindrance mechanism.…”
Section: Discussionsupporting
confidence: 67%
“…Glycosylation can modulate both the physical and biological properties of proteins (39,40) and aid in protein folding and secretion (41). Indeed, O-linked glycans on cellulase linkers confer proteolytic resistance (20,42) and have been shown to impart affinity to crystalline cellulose (21). Furthermore, it has been shown that small O-linked glycans exist on the TrCel7A CBM near the binding face ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the enzymatic activity of isolated CexCD toward cleavage of soluble substrates is similar to that of the full-length Cex, with or without linker glycosylation (32,54). Thus, neither the linker nor the cellulose-binding module alters the catalytic properties of the catalytic domain of Cex.…”
Section: Cex Is Composed Of Independent Catalytic and Cellulosebindinmentioning
confidence: 99%
“…Glycosylated Cex from S. lividans is reported to contain ϳ17 mol of mannose, with traces of galactose, per mole of protein (30,31). These differences are minor because samples of O-glycosylated Cex from C. fimi and S. lividans have very similar kinetic properties and are both resistant toward proteolytic degradation (31,32). Based on chemical shift, 15 N relaxation, and amide residual dipolar coupling (RDC) measurements, we demonstrate that the catalytic and cellulose-binding domains are physically independent and joined by a PT linker that is conformationally dynamic on the ns-to-ps time scale.…”
mentioning
confidence: 99%
“…Generally, it has been reported that glycosylation protects proteins from proteolysis. 28) In plant pathogens, protection of secreted enzymes from proteolysis might play an especially important role in the success of pathogen development in planta. 29) Another possible role of the N-terminal sequences of Bx-ENG-2 and Bx-ENG-3 is to contribute to forming a subunit, since Bx-ENG-2 and Bx-ENG-3 existed in a dimeric form, whereas Bx-ENG-1 without the extra sequence existed in a monomeric form.…”
Section: Discussionmentioning
confidence: 99%